2018
DOI: 10.4085/1062-6050-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Evaluating Aerobic Training and Common Sport-Related Concussion Outcomes in Healthy Participants

Abstract: Context Aerobic exercise interventions are increasingly being prescribed for concussion rehabilitation, but whether aerobic training protocols influence clinical concussion diagnosis and management assessments is unknown. Objective To investigate the effects of a brief aerobic exercise intervention on clinical concussion outcomes in healthy, active participants. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The bulk of the evidence supports the use of controlled aerobic exercise to safely treat concussion, [2][3][4][5][6] but there is little evidence to indicate which mode of aerobic exercise is the most effective. Patients are allowed to use the form of aerobic exercise they prefer as long they adhere to the target HR prescription intensity.…”
Section: Type and Volume Of The Exercise Prescriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the evidence supports the use of controlled aerobic exercise to safely treat concussion, [2][3][4][5][6] but there is little evidence to indicate which mode of aerobic exercise is the most effective. Patients are allowed to use the form of aerobic exercise they prefer as long they adhere to the target HR prescription intensity.…”
Section: Type and Volume Of The Exercise Prescriptionmentioning
confidence: 99%
“…3,4 Thus, a personalized exercise prescription for SRC treatment is derived ideally from the results of systematic graded exercise testing. [3][4][5][6] The target HR for the subsymptom threshold exercise training/treatment program is set at 90% of the HRt and is modified regularly (every few days to once a week) by retesting to establish a new HRt or by using clinical acumen to increase the target HR systematically according to the individual's level of exercise tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there were techniques that have not shown effectiveness in this context. For example, the study by Teel et al (16) showed that aerobic training had no significant effect on the clinical assessment of sports-related concussions in healthy participants. In the case of Brandt et al (36) , goal management training (GMT) tailored for children was not shown to be more effective than a psychoeducational control in improving parent-reported executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive rehabilitation training combined with hyperbaric oxygen therapy improved functional disorders and prognosis in patients with traumatic brain injury 6 Teel et al (16) , 2018…”
Section: Early Intensified Rehabilitation Training With Hyperbaric Ox...mentioning
confidence: 99%
See 1 more Smart Citation